Application of Bradford’s Law of Scattering to the Scientific Publications of Energy and Environment Research - Velmurugan, Chandran; Radhakrishnan, Natarajan (Engineering International, 2015)
This study has been made an attempt to describe the one of the most essential bibliographic laws i.e. Bradford law of scattering to test the scholarly publications of energy and environment in Australia. A total of 2802 papers published, out which 83.4% were journal articles and 99.7% were in the English language. According to Australian research, the output of Environmental Sciences Ecology (13.807%) account for the largest increase and it is occupied in the first place and Energy Fuels (6.208%) is in the 6th place during the present study. The three most productive journals with high citations were ‘Ecological Applications’ (= 4, 2721 citations), ‘Astrophysical Journal’ (= 44, 1614 citations), and ‘Monthly notes of the Royal Astronomical Society’ (= 38, 1389 citations) and the maximum number of citations contributed by ‘BAZZAZ FA’ from Harvard University, USA. In this study, based on the speculative aspects of Bradford’s Law of Scattering is tested and identified that the ratio depicts that it does not fit into the Bradford’s law of distribution.
Keywords: Scientometrics; Bradford’s Law; scholarly publications; energy and environment; Australian research; India; Australia